How Officials’ Competitive Pressure Affects Sustainable Development Capacity From a Spatial Perspective: Empirical Evidence From China - Xu, He; Wang, Kun; Li, Guoping; Zhang, Yufeng (Frontiers in Psychology, 2021)
The view of political achievements suggests that officials will prefer to implement measures that benefit their own development in order to seek promotions. In the past, GDP weighed heavily in officials' appraisals, leading them to develop the economy without regard to sustainability. Now that the central government has incorporated environmental indicators into the officials' appraisal system, will this lead officials to implement sustainable development strategies to the fullest extent? Are there spillover effects and regional heterogeneity in this role? This paper discusses these questions with the help of entropy method and a spatial Durbin model using data of 30 provincial-level regions in China from 2006-2016. The conclusions show that, firstly, the officials' competitive pressure is beneficial to enhance the sustainable development capacity of the province, but this effect is only effective in western China. Secondly, there is no spillover effect of officials' competitive pressure on sustainable development capacity; thirdly, foreign direct investment, the proportion of state-owned enterprises and environmental regulations have their own unique effects on sustainable development capacity, and there are spillover effects. Based on these findings, this paper proposes corresponding policy recommendations in terms of officials' appraisal system, talent training, foreign investment introduction, and state-owned enterprise reform.